Multicentric occurrence of multiple papillary thyroid carcinomas –HUMARA and BRAF mutation analysis. (17th April 2015) - Nakazawa, Tadao; Kondo, Tetsuo; Tahara, Ippei; Kasai, Kazunari; Inoue, Tomohiro; Oishi, Naoki; Mochizuki, Kunio; Kubota, Takeo; Katoh, Ryohei
<x xml:space="preserve">Abstract</x> Papillary thyroid carcinomas (PTCs) occasionally form multiple tumor nodules in the same gland. The aim of this study is to determine whether the foci arise from the same or different clonal origins. Our results may suggest that more than 30% of multiple PTCs independently occur. <boxed-text content-type="graphic" id="cam4466-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>